Kilmo Salama - Index-based Agriculture Insurance : A Product Design Case Study - International Finance Corporation (Washington, DC, 2015)
Farming is a mainstay of the Kenyan economy, representing three quarters of employment in the country. Nearly half of all farming output in the country is for subsistence purposes. Therefore, many farmers livelihoods are entirely dependent on their harvests, both for the income generated by selling crops and for feeding their families. Unfortunately, there is little certainty in subsistence farming since the size of the harvest is largely determined by the timing and amount of rainfall. The objective of this case study is to describe the design and implementation of an index-based agricultural insurance product targeting rural farmers in Kenya. The Kilimo Salama (Safe Agriculture in Kiswahili) product has been successful in protecting farmers against risks from drought or excessive rainfall, both of which can have disastrous effects on the harvest. The following sections present weather-related risks affecting farmers, the steps taken to address these problems by designing a new insurance product, the product development and implementation process, and the impact of this new product thus far. Beyond the focus on product design, this case also discusses lessons learned since the product's launch, how the product is expected to evolve in future versions, and scalability.